Cerebrospinal Fluid Viral Load and Neopterin in HIV-Positive Patients with Undetectable Viraemia. Issue 6 (August 2017) - Motta, Ilaria; Allice, Tiziano; Romito, Alessandra; Ferrara, Micol; Ecclesia, Sara; Imperiale, Daniele; Ghisetti, Valeria; Di Perri, Giovanni; Bonora, Stefano; Calcagno, Andrea
Background: Cerebrospinal fluid (CSF) HIV RNA is commonly used as a marker of compartmental antiviral activity in HIV-positive patients. Undetectable CSF HIV RNA levels have been associated with low CSF neopterin levels and better neurocognitive performances. The aim of this study was to analyse the prevalence and predictors of non-detectable CSF HIV RNA using a commercial assay. Methods: In adult HIV-positive HAART-treated patients with confirmed plasma HIV RNA <50 copies/ml, CSF HIV RNA (with Roche Amplicor Assay) and neopterin were measured. Results: 112 adult patients were included. Plasma and CSF HIV RNA were non-detectable (target not detected [TND]) in 29 (25.9%) and 36 (32.1%) patients, respectively. CSF TND was observed more frequently in patients with plasma TND ( P =0.005, OR=3.87). CSF neopterin levels were associated with age (rho =0.333, P =0.002) and current (rho= -0.272, P =0.015) and nadir (rho =-0.240, P =0.038) CD4 + T-lymphocytes; the lowest CSF neopterin concentration was observed in patients with CSF TND versus other viral load strata (0.62 mg/dl versus 0.78 mg/dl; P =0.048). Conclusions: Efficaciously treated HIV-positive patients with detectable plasma HIV RNA might imperfectly control CSF viral replication. Prospective studies addressing the management and neurocognitive consequences of CSF low-level viraemia are warranted.